Tony's bread : an Italian folktale - De Paola, Tomie (New York : Putnam, 1989)
A baker loses his daughter but gains a bakery in the grand city of Milano after meeting a determined nobleman and baking a unique loaf of bread.
"A Whitebird book."
Children's Catalog (Wilson)
Child Study Children's Book Committee
Booklist
3.2
K-3
Keywords: Bread -- Folklore; Folklore -- Italy; Bread -- Folklore; Folklore -- Italy